2020
DOI: 10.1111/liv.14614
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life, caregiver burden and mental health disorders in primary caregivers of patients with Cirrhosis

Abstract: Background and Aims Caregivers are needed for cirrhotic patients as there is progressive decline in cognition and self‐care. We intend to study the quality of life (QOL), psychosocial burden and prevalence of mental health disorders among caregivers. Methods Cross‐sectional study where caregivers, defined as person who takes responsibility of providing care to patient, of cirrhotic patients were included. Short form 36 health survey (SF‐36) to assess QOL, Zarit Burdern Index12 (ZBI) for caregiver burden (CB). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…In one cross‐sectional study from India of 132 caregivers of patients with cirrhosis, 25% reported that they had to return to work due to increasing family financial constraints. [ 27 ] In the 2011 study by Bajaj et al [ 33 ] of 104 caregivers of patients with cirrhosis, 79% of caregivers reported that they did not have any support for financial advice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In one cross‐sectional study from India of 132 caregivers of patients with cirrhosis, 25% reported that they had to return to work due to increasing family financial constraints. [ 27 ] In the 2011 study by Bajaj et al [ 33 ] of 104 caregivers of patients with cirrhosis, 79% of caregivers reported that they did not have any support for financial advice.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies, patients and/or caregivers reported that they had to reduce spending on their children's education to afford medical care. [ 24,27,33 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers commonly report a wide variety of physical and psychological symptoms of their own. 15 Data from the Tianjin Municipal Government of China in 2017 showed that the average age among caregivers of disabled elderly adults had reached 59.47 years. 16 Studies have shown that there are many problems regarding family members’ caregiving behaviour, such as a lack of professional knowledge, lack of caregiving skills and lack of social support resources, which may because family members are not professional caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 ] Caregivers report a high level of emotional distress and impaired quality of life (QoL) as a result of the psychosocial burden incurred when caring for those with cirrhosis. [ 5 ]…”
Section: Introductionmentioning
confidence: 99%